Consumer satisfaction with halal hub MSME services: evidence from Sumenep regency, Indonesia - Alvianita, Nuri; Destiarni, Resti Prastika; Suprapti, Isdiana (LPPM ISNJ Bengkalis, 2025)
Purpose – The research aims to identify business actors' satisfaction with services and analyze the attributes influencing service quality at the halal hub MSME Sumenep. Method – The quantitative research involves 60 respondents, selected using purposive sampling with criteria who had received assistance from the halal hub MSME Sumenep. The data source used is primary data collected through structured questionnaires distributed directly to respondents. The methods used for the analysis are the CSI (customer satisfaction index) and IPA (importance performance analysis). Findings – The CSI analysis results indicate that business actors were very satisfied. Meanwhile, the results of the IPA analysis in quadrant I show three priority improvement attributes: completing administration on time, being ready to serve at any time during working hours and helping obtain certification. The IPA matrix also revealed attributes in Quadrant II that should be maintained due to their strong performance and perceived importance. In contrast, attributes in Quadrants III and IV represent lower strategic priority. Enhanced satisfaction is expected to foster user loyalty and generate positive word-of-mouth among other MSMEs. MSME satisfaction will make the business ask for services from halal hub again and even recommend these services to other MSMEs. Implications – Theoretically, these findings support the notion that service quality is shaped by users' perceptions of both performance and the importance of service attributes. Empirically, the study provides practical insights into halal support institutions in designing service improvements that align with business actors' expectations.